Pengaruh Dana dan Waktu Dosen terhadap Minat Meneliti: Studi Kasus Universitas Bina Nusantara - Muljo, Hery Harjono (Bina Nusantara University, 2012)
Few numbers of lecturers who did research is a big question of why it happens. It is provisionally estimated that research funds offered and limited time to do such led some lecturers did not do their obligations. This raises the question of whether research funds affected the lecturerâs interests in researching or limited time of a lecturer affected the interests of a lecturer to do a research. The aim of this study is to find out either the funds or the time affected the interests of lecturers to do a research. This study used quantitative, nonexperimental methods. There are two independent variables and one dependent variable in this study. The X1 represents the funds, and the X2 represents the time. While the Y variable represents the interest in researching. The study results show that both funds and time have a weak correlation to the interests in researching, and funds have a weak correlation over time. Moreover, based on the results of hypothesis testing between funds (X1) and time (X2) show that there is no significant relationship exists between funds (X1) and time (X2). It means that there is a negative correlation, weak and insignificant.